2018
DOI: 10.21037/jtd.2018.11.03
|View full text |Cite
|
Sign up to set email alerts
|

Detection of epithelial growth factor receptor (EGFR) mutations on CT images of patients with lung adenocarcinoma using radiomics and/or multi-level residual convolutionary neural networks

Abstract: Background: We aim to analyze the ability to detect epithelial growth factor receptor (EGFR) mutations on chest CT images of patients with lung adenocarcinoma using radiomics and/or multi-level residual convolutionary neural networks (MCNNs). Methods: We retrospectively collected 1,010 consecutive patients in Shanghai Chest Hospital from 2013 to 2017, among which 510 patients were EGFR-mutated and 500 patients were wild-type. The patients were randomly divided into a training set (810 patients) and a validatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 36 publications
(44 reference statements)
2
37
0
Order By: Relevance
“…Previous articles on pulmonary tumor radiomics were generally based on non-contrast CT images (20)(21)(22). Some studies have used contrast images alone (23,24), and some have used both, but no comparisons or descriptions regarding which type of image is better for further analysis have been reported (25).…”
Section: Discussionmentioning
confidence: 99%
“…Previous articles on pulmonary tumor radiomics were generally based on non-contrast CT images (20)(21)(22). Some studies have used contrast images alone (23,24), and some have used both, but no comparisons or descriptions regarding which type of image is better for further analysis have been reported (25).…”
Section: Discussionmentioning
confidence: 99%
“…Although Liu et al [27] and Rizzo et al [29] achieved relatively higher AUC scores of 0.709 and 0.82, respectively, their studies did not include independent testing groups which are essential to establishing the robustness of predictive models. Xiong et al [23] and Li et al [19] showed impressive results by using 3D deep learning model trained from scratch and achieved AUC scores of 0.776 and 0.809, respectively. Our model was trained and validated using the same patient cohort as Li's work [19] and, in an independent testing group, achieved a higher AUC score than any previously published study in this area.…”
Section: Discussionmentioning
confidence: 99%
“…Xiong et al [23] and Li et al [19] showed impressive results by using 3D deep learning model trained from scratch and achieved AUC scores of 0.776 and 0.809, respectively. Our model was trained and validated using the same patient cohort as Li's work [19] and, in an independent testing group, achieved a higher AUC score than any previously published study in this area. Notably, the lowest-performing model in our study (a fine-tuned 2D CNN using the large input size and transverse slicing method) achieved a lower AUC (0.642) than any prior studies, highlighting the importance of optimally selecting the methods used to construct CNNs for medical applications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach is a non-invasive and easy-toimplement deep learning method. Other studies (27)(28)(29) also show that deep learning models can identify gene mutations in lung cancer.…”
Section: Original Articlementioning
confidence: 95%